A novel configuration of electrical double layer capacitor with plastic crystal based gel polymer electrolyte and graphene nano-platelets as electrodes: A high rate performance. (1st February 2015) - Singh, Manoj K.; Suleman, Mohd; Kumar, Yogesh; Hashmi, S.A.
Abstract: A new, symmetrical, high rate, solid-state EDLC (electrical double layer capacitor) has been fabricated employing a plastic crystal SN (succinonitrile) based GPE (gel polymer electrolyte) and GNPs (graphene nano-platelets) as electrodes. The free-standing GPE film containing poly(vinylidene fluoride-co-hexafluoropropylene) (PVdF-HFP) exhibits the excellent suitability as electrolyte in EDLC due to its high ionic conductivity (∼2 × 10 −3  S cm −1 at 20 °C), thermal stability (from −30 to 80 °C), electrochemical stability window (∼3.5 V vs. Ag), and excellent mechanical properties. The high rate capability of the EDLC has been observed from the impedance analysis in terms of high knee frequency (∼58 Hz), low response time (∼791 ms) and high pulse power (∼16.4 kW kg −1 ). The cyclic voltammetric response indicates the capacitive performance up to a substantially high scan rate of 1000 mV s −1, which further confirms the high rate performance of the EDLC. Though the specific energy of the solid-state EDLC is observed to be low (Emax  ∼ 8.2 Wh kg −1 ), its power density is substantially high (Pmax  > 4 kW kg −1 ). After ∼20% decrement in specific capacitance during the initial charge–discharge cycles, the EDLC offers almost stable performance up to ∼3500 cycles. Highlights: Solid-state, flexible EDLC is reported with graphene nano-platelet electrodes and GPE. Plastic crystal based gel electrolyte is used for EDLC fabrication for the first time. Graphene/gel electrolyte interfaces show good capacitance with high rate performance.